Viscosity and viscoelasticity of osteoarthritic synovial fluids in comparison to intraarticular injection of hyaluronic acid (Synvisc and Suplasyn) - Abd. Rahim, Nour El Huda; Zulkifly, Ahmad Hafiz; Mohamed, Farahidah; Ku Zaifah, Norsidah (Malaysian Medical Associations, 2012)
BACKGROUND: Osteoarthritis is a debilitating degenerative disease of the old age . One of the pathophysiology is that the synovial fluids (SF) are reduced due to the lowered concentration, reduced molecular weight of hyaluronic acid, thus reducing the viscoelasticity of the SF. Apart from the pharmacological treatments, intraarticular injection of hyaluronic acid (IAHA) was introduced as a viscosupplement in osteoarthritic patients to restore the viscoelasticity of the synovial fluids, give symptomatic relief of joint pain and delay the total joint arthroplasty. OBJECTIVE: To evaluate the viscosity and viscoelasticity of osteoarthritic SF with the aim to compare with IAHA; Synvisc (high molecular weight IAHA) and Suplasyn (low molecular weight IAHA). MATERIALS AND METHOD: The osteoarthritic SF was obtained from consented patients undergone total knee arthroplasty. The viscosity and the viscoelasticity of IAHA and osteoarthritic SF were analyzed at different temperatures (25, 37 and 40°C) using ThermoHaake rheometer. RESULTS: The flow curves constructed showed that osteoarthritic SF and both IAHA exhibited non-Newtonian shear thinning (pseudoplastic) fluid behaviour. The osteoarthritic SF had the lowest viscosity compared to IAHA. By increasing the temperatures, the viscosity of the IAHA and osteoarthritic SF were reduced. In the viscoelasticity test, the storage/elastic modulus of osteoarthritic SF and Synvisc were more dominant than the loss/viscous modulus. Unlike Suplasyn, the viscous modulus was more pronounced than the elastic modulus in all temperatures. CONCLUSION: At human body temperature, 37°C, both viscosupplements and osteoarthritic synovial fluids shared the same pseudoplastic type of non-Newtonian fluid. Synvisc and osteoarthritic SF showed elastic like behaviour more prominent than the viscous like behaviour opposite to Suplasyn. The rheological behaviour of Suplasyn and Synvisc with osteoarthritic SF were different because of the differences between the molecular weight of the hyaluronic acid and the network forming ability.